1994
DOI: 10.1021/bi00174a009
|View full text |Cite
|
Sign up to set email alerts
|

GTPase Activation of ATP Sulfurylase: The Mechanism

Abstract: ATP sulfurylase from Escherichia coli K12 catalyzes two, coupled reactions: the hydrolysis of GTP and the formation of activated sulfate (APS). At saturating levels of GTP, the initial rate of APS formation is stimulated 116-fold. The mechanism of this activation has been investigated using isotope trapping, mass spectrometry, and initial velocity kinetic techniques. In the presence of GTP, APS formation proceeds via nucleophilic attack of sulfate at the alpha-phosphoryl group of ATP. Isotope-trapping experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…We have previously shown that GTP and ATP bind randomly to the enzyme and that GTP is hydrolyzed in the absence of activators Liu et al, 1994). Hence, the allosteric model used in the interpretation of the current results is one in which GTP and the activator bind randomly to the enzyme, and the substrate complexes with and without activator can produce product (see Figure 1).…”
Section: Resultsmentioning
confidence: 72%
“…We have previously shown that GTP and ATP bind randomly to the enzyme and that GTP is hydrolyzed in the absence of activators Liu et al, 1994). Hence, the allosteric model used in the interpretation of the current results is one in which GTP and the activator bind randomly to the enzyme, and the substrate complexes with and without activator can produce product (see Figure 1).…”
Section: Resultsmentioning
confidence: 72%
“…[ 35 S]-PAPS was purified chromatographically by anion exchange HPLC (AX300, SynChropak) using an isocratic eluant (NaPO 4 , 0.30 M, pH 6.4). The purified [ 35 S]-PAPS was desalted and concentrated to dryness as described previously (32). The compounds was dissolved in Hepes (50 mM, pH 8.0) and stored at −70°C.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of helix-induction by TFE is not fully understood and is debated in current literature [4][5][6]. More recently, the effect of TFE on the structure of intact proteins was investigated using circular dichroism (CD) and proton nuclear magnetic resonance (NMR) spectroscopy [7][8][9][10]. The general observation emerged from these studies is that the TFEinduced state of a protein is characterized by a significant content of helical secondary structure, but lacking the specific tertiary interactions of the native protein.…”
Section: Introductionmentioning
confidence: 99%